Ответ:
Объяснение:
a^2/3 - 3a^3/2 -3 = (2a^2 - 9a^3 - 3 * 6)/6 = (2 * (-2)^2 - 9*(-2)^3 - 18)/6 =
=(8 + 72 - 18)/6 = 62/6 = 10 1/3
[tex]\displaystyle\bf\\\frac{a^{2} }{3} -\frac{3a^{3} }{2} -3=\frac{1}{3} a^{2} -1,5a^{3} -3\\\\\\a=-2\\\\\\\frac{1}{3} a^{2} -1,5a^{3} -3=\frac{1}{3} \cdot(-2)^{2} -1,5\cdot(-2)^{3} -3=\frac{1}{3} \cdot 4-1,5\cdot(-8)-3=\\\\\\=\frac{4}{3} +12-3=1\frac{1}{3} +9=10\frac{1}{3} \\\\\\Otvet \ : \ 10\frac{1}{3}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
a^2/3 - 3a^3/2 -3 = (2a^2 - 9a^3 - 3 * 6)/6 = (2 * (-2)^2 - 9*(-2)^3 - 18)/6 =
=(8 + 72 - 18)/6 = 62/6 = 10 1/3
[tex]\displaystyle\bf\\\frac{a^{2} }{3} -\frac{3a^{3} }{2} -3=\frac{1}{3} a^{2} -1,5a^{3} -3\\\\\\a=-2\\\\\\\frac{1}{3} a^{2} -1,5a^{3} -3=\frac{1}{3} \cdot(-2)^{2} -1,5\cdot(-2)^{3} -3=\frac{1}{3} \cdot 4-1,5\cdot(-8)-3=\\\\\\=\frac{4}{3} +12-3=1\frac{1}{3} +9=10\frac{1}{3} \\\\\\Otvet \ : \ 10\frac{1}{3}[/tex]